Collective enhancement of numerical acuity by meritocratic leadership in fish - Bisazza, Angelo (Nature Publishing Group, 2014)
It has been known for more than a century that interacting people can generally achieve more accurate decisions than single individuals. Here we show that interacting guppy fish (Poecilia reticulata) achieve a superior level of numerosity discrimination well beyond the average ability of the isolated individual fish. This enhancement of numerical acuity was observed in dyadic interactions when (Experiment 1) the dyad chose which larger shoal of guppies to join and when (Experiment 2) the dyad chose the higher or the lower numerosity among two decision options after having learned the task individually. Dyadic accuracy and that of the more competent member of each dyad matched closely, supporting the hypothesis that meritocratic leadership arises spontaneously between dyadically interacting fish, rather than the ‘many wrongs' principle that has been used to explain group superiority in many species.